2000
DOI: 10.1046/j.1365-2044.2000.01420.x
|View full text |Cite
|
Sign up to set email alerts
|

Increases in serum concentrations of cardiac proteins and the prediction of early postoperative cardiovascular complications in noncardiac surgery patients

Abstract: SummaryWe investigated the use of measurements of serum concentrations of the cardiac proteins troponins I and T as biochemical markers of myocardial cell damage in 80 patients undergoing vascular or major orthopaedic surgery. Holter electrocardiographic monitoring was carried out before surgery and for 3 days after surgery. Blood samples for troponins I and T and creatine kinase-MB isoenzyme were taken on each of these 4 days. Outcome was assessed at 3 months using a patient questionnaire, general practitione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 18 publications
1
37
0
3
Order By: Relevance
“…Serial assays of creatine kinase (CK), creatine phosphokinase (CPK), serum myoglobin, and cardiac troponin I are laboratory tests of choice for the diagnosis of myocardial injury. Various authors report changes in these serum markers as a result of skeletal muscle injury, which also correlates with surgical incision length, surgical approach, and operative time [12,16,18,20,21,24]. These reports confirm elevations in CK, CPK, and serum myoglobin can occur after orthopaedic surgery in the absence of overt clinical manifestations of myocardial injury.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Serial assays of creatine kinase (CK), creatine phosphokinase (CPK), serum myoglobin, and cardiac troponin I are laboratory tests of choice for the diagnosis of myocardial injury. Various authors report changes in these serum markers as a result of skeletal muscle injury, which also correlates with surgical incision length, surgical approach, and operative time [12,16,18,20,21,24]. These reports confirm elevations in CK, CPK, and serum myoglobin can occur after orthopaedic surgery in the absence of overt clinical manifestations of myocardial injury.…”
Section: Introductionmentioning
confidence: 77%
“…Reported use of blood enzyme markers is common throughout the surgical literature [9,12,[16][17][18][20][21][22][23][24]. Rhabdomyolysis has numerous etiologies and includes local crush injury, vascular compromise, soft tissue infections, electrical injuries, excessive steroid use, seizures, surgery, and heat stroke [1,19,22].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore Landesberg et al [5] have shown that prolonged postoperative myocardial ischaemia (> 30 min) is an independent predictor of long-term mortality following major vascular surgery. Postoperative myocardial ischaemia has also been associated with major cardiovascular complications within three months of surgery in patients undergoing both major and intermediate risk surgery [7]. SMI may also be predictive of adverse cardiovascular events up to a year after a range of non-cardiac surgical operations [6].…”
mentioning
confidence: 99%
“…Enzim sonuçlarındaki anlamlı fark klinik olarak iskemi epizodlarının süresinde de gözlenmiştir. Ancak, troponin düzeyleri, yayınlarda "majör kardiyak olayı" öngörüsünde ulaşacağı seviyeden oldukça düşük bulunmuştur (17)(18)(19) . Biccard ve ark.…”
Section: Analjezik Gereksinimiunclassified